2004
DOI: 10.1086/422721
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections in Travelers: Implications for Prevention and Control

Abstract: Sexually transmissible diseases (STDs), the most common notifiable infectious conditions, remain major threats to reproductive and public health worldwide. Travelers are particularly vulnerable to STDs, because of voluntary or involuntary sexual behavior while abroad, and are significant vectors who introduce new pathogens and resistant strains to unaffected parts of the world. This article outlines some key issues that travel medicine specialists and other clinicians should revisit when providing services to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
0
27
0
3
Order By: Relevance
“…A study exploring STIs in travellers stated that HIV related to travelling was the most common STI. While in regions like Asia and Africa, migrant labours, sex workers and truck drivers travelling long distance maintain the HIV epidemic, in Europe there have been increasing numbers of new HIV cases over the years attributable mostly to travel [23]. Although this paper also covers the role of power in sexual behaviour of tourists and tourism workers, no other studies were found that discussed this factor.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A study exploring STIs in travellers stated that HIV related to travelling was the most common STI. While in regions like Asia and Africa, migrant labours, sex workers and truck drivers travelling long distance maintain the HIV epidemic, in Europe there have been increasing numbers of new HIV cases over the years attributable mostly to travel [23]. Although this paper also covers the role of power in sexual behaviour of tourists and tourism workers, no other studies were found that discussed this factor.…”
Section: Discussionmentioning
confidence: 96%
“…In regards to risk taking behaviour of travellers, another study suggested that travellers taking sexual risk were more likely to not practise safe sex regardless of the place of destination [23]. The latter study also reported that 5-50% of travellers travelling short term engage in casual sex [23].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations